Pangenome-assisted development and validation of a predictive KASP marker for the barley leaf rust resistance gene Rph7 - Wiles, Danielle; Gurung, Kshamata; Tongson, Eden; Park, Robert F.; Cai, Yu; Viradia, Bhavya; Okuda, Kazuhide Shaun; Perovic, Dragan; Dracatos, Peter M. (Frontiers in Agronomy, 2025)
IntroductionBarley leaf rust (BLR), caused by Puccinia hordei, is a devastating fungal disease that significantly reduces barley (Hordeum vulgare subsp. vulgare) yields worldwide. Genetic resistance offers an effective and sustainable control strategy; however, reliance on single resistance genes often results in the rapid breakdown of resistance due to the emergence of virulent P. hordei races. Durable resistance in elite, high-yielding cultivars requires pyramiding multiple genes with diverse mechanistic actions. To achieve this, predictive molecular markers are essential for tracking individual resistance genes throughout the breeding cycle. Unlike most classical major resistance genes in the Triticeae, the recently cloned Rph7 gene encodes a NAC transcription factor containing a zinc-finger BED domain that mediates a novel, pathogen-induced resistance mechanism by enhancing basal defence. Rph7 represents a valuable target for gene-stacking strategies, particularly when deployed in combination with other effective BLR resistance genes.MethodsTo support predictive marker-assisted selection, three single-nucleotide polymorphisms located within the conserved flanking gene HvPG1 were converted into Kompetitive Allele Specific PCR (KASP) co-dominant markers.Results and discussionThese markers were validated across a core panel of barley accessions known to either lack or contain Rph7 resistance, with the best performing marker subsequently evaluated in 173 accessions, including lines from the latest pangenome, elite Australian and international cultivars, and experimental lines carrying or lacking Rph7. One marker was deemed a reliable, breeder-friendly, high-throughput KASP marker for tracking Rph7 resistance, enabling the efficient development of BLR-resistant cultivars and supporting improved disease management in barley breeding programs.